Heavy metal concentrations and ecological risk assessment of the suspended sediments of a multi-contaminated Brazilian watershed - Yuri Jacques Agra Bezerra da Silva; José Ramon Barros Cantalice; Vijay Pal Singh; Clístenes Williams Araújo do Nascimento; Bradford Paul Wilcox; Ygor Jacques Agra Bezerra da Silva (Acta Scientiarum. Agronomy, 2019)
Metal concentrations in suspended sediments of one of the most polluted rivers in Brazil were measured. Concentrations of Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn were determined by inductively coupled plasma while Hg and As were analyzed with hydride generation flow injection atomic absorption spectroscopy. Contamination of As, Cd, Cr, Cu, Fe, Hg, Mn, Ni, Pb, and Zn was assessed using pollution indices, ecological risk assessment, statistical multivariate techniques and comparison with sediment quality guidelines. Suspended sediments of the upstream portion of the Ipojuca River are moderately contaminated, especially with Mn and As. On the other hand, sediments of the downstream section are highly contaminated, mainly with Zn, Pb, and As. Furthermore, the mean Ei (potential ecological risk) values of Pb and As showed considerable ecological risk in the downstream cross section. The comparison of our data with sediment guideline values indicated that the concentrations of Mn and Pb in the upstream section of the Ipojuca River pose a risk to sediment-dwelling organisms, while Pb and Zn are the metals of concern in the downstream section.